E- Counsellor A customizable real time mobile application for studying the human behavior to manage the amount of stress generated at work location - Vishwakarma, Seema Bhim; Amondkar, Madhavi Dilip (IJRDO -Journal of Computer Science Engineering, 2016)
E-counsellor is a mobile based application proposed in the paper with an attempt to alleviate thestress of an individual depending upon the responses entered by him. Techniques used forextracting and understanding the level of stress and relieving measures are normally being usedby Counsellors for respiting an individual from stress. The proposed mobile based applicationmakes use of neural network algorithm which works like a human brain and the apt solution orremedies are suggested. In today’s world of heavy work load and personal responsibilities peopledon’t visit Counsellors in spite of identifying the need for it. The application proposed in thepaper is a mobile app which could be used on a daily basis. The paper concentrates on one areaof stress that is related to working environment. The causes of working stress are depicted basedon the details gathered from the Counsellor. The proposed system deals with step by step guidelike a manual Counsellor for suggesting measures based on neural network which will help aperson to relieve stress and motivate an individual. The successful implementation of the project